Kilka słów o antidotach stosowanych w starożytności - Lampkowska, Paulina (Studia Europaea Gnesnensia, 2011)
The most renown cases of using and concocting antidotes in antiquity. Quoting more or less credible recipes for making antitoxins based on translated fragments of antique works. Placing the phenomenon in a broad context of social aspect and mores.